Study on Unsteady Triple-Shock Configurations in Supersonic Flows Past Combined Cylinder AD Bodies in Different Gas Media - Azarova, Olga; Gvozdeva, Ludmila; Kravchenko, Oleg (New Approaches in Engineering Research Vol. 12, 2021)
The paper is devoted to the control of supersonic flows past aerodynamic bodies under the action of external energy deposition. Mechanism of the interaction of a bow shock over a body with the oblique shock resulting from the refraction of the bow shock at the external energy source surface is revealed. Different types of shock waves intersection might appear in this process, among them are triple-shock configurations. The objectives of this paper are the investigations of unsteady triple-shock configurations in the vicinity of the surface of combined cylinder bodies “hemisphere-cylinder” and “hemisphere-cone-cylinder” under the action of external energy deposition and their effect on the body surface pressure. The studies have been conducted numerically using inviscid approach on a base of the Euler equations at M=4 for gaseous media with ratio of specific heats 1.4 and 1.2. Complex conservative difference schemes are used in the simulations. Dependences of the angles of triple-shock configuration on the rarefaction degree in an energy source and on the incident shock angle have been obtained. Generation of local space-time areas with increasing boundary pressure has been established. Mechanism of boundary pressure growth together with local front drag force increase is shown to be connected with a vortex action as well as the action of the arising shock segments in the vicinity of triple-shock configuration. Also, the comparison with the plane flow symmetry has been conducted. The results can be used for organization of flow control via external energy deposition by means of laser, microwave or electrical discharge.